Auditory Sensory Memory and the Cholinergic System: Implications for Alzheimer's Disease - Pekkonen, Eero; Hirvonen, Jyrki; Jääskeläinen, Iiro P.; Kaakkola, Seppo; Huttunen, Juha (NeuroImage (Orlando, Fla.), 2001)
Auditory sensory memory represents one of the simplest types of short-term memory that can be studied electrophysiologically with mismatch negativity (MMN); a specific auditory event-related potential indexing automatic comparison of incoming stimuli to an existing memory trace. Previous results suggest that auditory sensory memory deteriorates in aging and especially in Alzheimer's disease (AD). It has remained unsettled, however, whether MMN is regulated by the cholinergic system, which is deteriorated in AD contributing to cognitive impairments. We recorded cortical auditory responses with a magnetometer from 13 healthy subjects after intravenous injection of scopolamine, centrally acting cholinergic antagonist, or glycopyrrolate, a drug with a peripheral anticholinergic properties without penetrating the blood–brain barrier, using a double-blind protocol. Scopolamine reduced MMNm amplitude in response to frequency, but not duration, change, increased P50m amplitude, and delayed N100m latency. These findings suggest that the cholinergic system regulates the frequency-specific comparison of incoming stimuli to existing memory trace and modulates the preattentive processing related to stimulus detection. Further, neural mechanisms responsible for cortical frequency- and duration-specific discrimination appear to have different sensitivities to cholinergic modulation. Auditory evoked potentials might be suitable to monitor cholinergic activity in AD.